2020
DOI: 10.1136/bmjdrc-2020-001426
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload is related to elevated blood glucose levels in obese children and aggravates high glucose-induced endothelial cell dysfunction in vitro

Abstract: IntroductionThis study was performed to investigate the role of iron overload in the early stage of hyperglycemia-induced vascular functional impairment.Research design and methodsA total of 196 obese children were enrolled, and data regarding ferritin levels, blood glucose levels, intima-media thickness of carotid arteries, liver function and fibrosis index, hemoglobin, blood pressure, blood lipids, and inflammation indicators were collected. Ferritin levels were compared with a control group, which consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Experimental studies have provided some insight into the cooperative effects of hyperglycemia and increased iron. Ferritin could aggravate cell damage and dysfunction in cells cultured with high glucose by nuclear factor-κB activation, inflammatory response, lipopolysaccharide-mediated signaling pathway, protein kinase B signaling, and regulation of nitric oxide biosynthesis [19]. Excessive iron increased markers of ferroptosis and lipid reactive oxygen species in brain microvascular endothelial cells from diabetic animals [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have provided some insight into the cooperative effects of hyperglycemia and increased iron. Ferritin could aggravate cell damage and dysfunction in cells cultured with high glucose by nuclear factor-κB activation, inflammatory response, lipopolysaccharide-mediated signaling pathway, protein kinase B signaling, and regulation of nitric oxide biosynthesis [19]. Excessive iron increased markers of ferroptosis and lipid reactive oxygen species in brain microvascular endothelial cells from diabetic animals [20].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported elevated serum ferritin is related to poorer prognosis of ischemic stroke [14-17], whereas other study found higher serum ferritin could not predict functional disability at 3 months [18]. Besides, high iron status may have a cooperative effect on the process of cell damage and dysfunction induced by hyperglycemic status [19, 20]. Our previous study reported acute iron overload affects mortality and neurologic deficits at 24 h after transient focal ischemia in rats with hyperglycemia [21].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main sources of endothelial oxidative stress and inflammation is hyperglycemia, and iron overload aggravates endothelial dysfunction caused by hyperglycemia (Wu et al, 2020). Iron overload enhances oxidative stress and the NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome signaling, triggering the evolution of several inflammatory mediators, resulting in a cascade of inflammatory responses and renal dysfunction in ironoverloaded rats (Chaudhary et al, 2018).…”
Section: Iron Overloadmentioning
confidence: 99%
“…4,49 Epidemiological studies have also shown that elevated serum ferritin or iron overload are associated with higher levels of plasma glucose, diastolic blood pressure, uric acid and IR. 50,51 Thus, as schematically summarized in Figure 1, it is reasonable to hypothesize that ferroptosis is closely related to obesity, T2DM or other coexisting metabolic disorders that occur with MAFLD.…”
Section: Other Metabolic Risk Factorsmentioning
confidence: 99%